Pengaruh Intelectual Capital terhadap Kinerja Keuangan Perusahaan Farmasi yang Terdaftar pada Bursa Efek Indonesia Tahun 2009-2013 - Andriyani, Ria (Universitas muhammadiyah palembang, 2014)
The problem construction is how does the influence of IC to the performance of pharmaceutical company finance which is registered at BEI in 2009-2013. The aim of this research is to know how big is the influence of IC to theperformance of this company in 2009-2013. This research is associative. The reseach unit is BEI. The variable of IC is measured by VACA, VAHU, and STVA, meanwhile the financial performance is measured by ROA, ROE,and EP. The data which is needed is the survey. The method of collecting data is documentation. The analysis of data uses the descriptive statistics and inferential which is used with the model of double linear regression. The result of this research shows that IC is significant to financial performance inhypotheses test of F, whereas, VACA gives the positive influence with ROE and the negative influence with ROA and EP in hypotheses test of t. Then for VAHU, the result which is reached gives the positive significant influence to the whole of indicator in financial performance. Otherwise, for the result which is reached by STVA is not significant to ROA, ROE, and EP.